Microinvasive carcinoma of the uterine cervix in a 14-year-old adolescent: case report and literature review - Gonçalves, Carla Vitola; Quintana, Silvana Maria; Marcolin, Alessandra Cristina; Duarte, Geraldo; Costa, Juvenal Soares Dias da; Karam, Fabine; Bianchi, Mônia Steigleder (São Paulo Medical Journal, 2009)
CONTEXT: Cancer of the uterine cervix is rare during adolescence. The reported rates are 0/100,000 adolescents aged 10 to 19 years and 1.7/100,000 women aged 20 to 24 years. However, several studies have shown increasing incidence of preneoplastic lesions at increasingly early ages. CASE REPORT: This paper reports a case of microinvasive carcinoma of the uterine cervix in a 14-year-old patient with menarche at 10 years of age and first coitus at 12 years of age. The objective of the present report was to alert gynecologists and pediatricians regarding the need for cervical carcinoma prevention among sexually active adolescents, based on educational programs that explain the purpose of colpocytological examinations and encourage their use, along with condom use and limitation of the number of sexual partners.